2017
DOI: 10.1161/circimaging.116.005711
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Echocardiography to Estimate Pulmonary Artery Pressures With Exercise

Abstract: Background Exercise echocardiography is often applied as a noninvasive strategy to screen for abnormal pulmonary hemodynamic response, but it is technically challenging and limited data exist regarding its accuracy to estimate pulmonary arterial pressure (PAP) during exercise. Methods and Results Among 65 patients with exertional intolerance undergoing upright invasive exercise testing, tricuspid regurgitation (TR) Doppler estimates and invasive measurement of PAP at rest and peak exercise were simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
59
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 46 publications
3
59
0
4
Order By: Relevance
“…The strength of this study is, that the investigators performed echocardiography and right heart catheterization simultaneously. The study showed high correlations of invasive and noninvasive assessments, both at rest and during exercise, as long as TRV signals revealed a good quality (9). At rest in 68% of patients TRV Doppler envelopes revealed a high quality and highly correlated with the invasive measurements.…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…The strength of this study is, that the investigators performed echocardiography and right heart catheterization simultaneously. The study showed high correlations of invasive and noninvasive assessments, both at rest and during exercise, as long as TRV signals revealed a good quality (9). At rest in 68% of patients TRV Doppler envelopes revealed a high quality and highly correlated with the invasive measurements.…”
mentioning
confidence: 65%
“…In conclusion, the paper of van Riel et al (9) represents an important step forward in the awareness of possibilities and limitations of transthoracic Doppler-echocardiography for the evaluation of the pulmonary circulation. However, more research and evidences are urgently needed to test the reliability of TRV assessment in different clinical settings and to settle its standardization.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…In the study by van Riel et al, the authors compared the use of Doppler echocardiography to right-heart catheterisation at detecting PHT in a cohort of patients presenting with exertional intolerance but no prior history of PHT (11). The tricuspid regurgitation (TR) signals on Doppler echocardiogram were used for pulmonary artery pressure (PAP) calculations, which include systolic pulmonary artery pressure (SPAP) estimation from peak TR velocity and MPAP estimation from the TR velocity-time integral envelop.…”
mentioning
confidence: 99%